Demeanor of rivaroxaban in activated/inactivated FXa - Kaname Seki; Yosuke Mizuno; Toku Sakashita; Shintaro Nakano; Jun Tanno; Yasushi Okazaki; Toshihiro Muramatsu; Shigeyuki Nishimura; Takaaki Senbonmatsu (Elsevier, 2017)
Activated factor X (FXa) plays an important role in thrombin generation and inflammation. Factor X is not converted constitutively to FXa, but only after intrinsic clotting factors are activated and/or cellular injury occurs. Although rivaroxaban is one of direct FXa inhibitors, its function in the inactivated coagulation cascade is unclear. In human umbilical vein endothelial cells that natively express protease-activated receptor-1 and -2, high dose rivaroxaban did not alter gene transcripts including pro-inflammatory genes in DNA microarray. Upon FXa stimulation, the expressions of pro-inflammatory genes such as monocyte chemoattractant protein-1 (MCP-1), intracellular adhesion molecule-1, and interleukin-8 were maximally increased at 4 h after stimulation, and were suppressed by rivaroxaban. To confirm these results, quantitative polymerase chain reaction and enzyme-linked immunosorbent assay (ELISA) for MCP-1 were performed. FXa evoked the expression of MCP-1 maximally at 4 h after stimulation, whereas MCP-1 displayed a different temporal activation in ELISA. Interestingly, rivaroxaban inhibited both time courses of MCP-1 expression. These results suggest that rivaroxaban may not influence gene modulation in the inactivated coagulation state, but can attenuate the endothelial damage evoked by FXa and pro-inflammatory cytokine genes.